2020
DOI: 10.3892/etm.2020.8483
|View full text |Cite
|
Sign up to set email alerts
|

Meta‑analysis on the use of hyaluronic acid gel to prevent intrauterine adhesion after intrauterine operations

Abstract: Intrauterine adhesion (IUA) is a severe complication that occurs following abortion, and hyaluronic acid gel has been used to prevent IUA following intrauterine operation. The present study aimed to systematically evaluate the efficacy of hyaluronic acid gel in preventing IUA following intrauterine operation. In the current study, a literature search was performed using PubMed, Cochrane Library and EMbase databases for randomized controlled clinical trials that used hyaluronic acid gel as an adjuvant therapy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…The efficiency of the hyaluronic gel was independent to the type of procedure, these figures being as follows: abortion, hysteroscopy, primary disorders/diseases such as abortion, IUA, submucosal myoma, endometrial polyps or mediastinum uterus. Furthermore, the hyaluronic gel improved pregnancy rates [ 132 ].…”
Section: Introduction Our Current Knowledge About the Asherman Symentioning
confidence: 99%
“…The efficiency of the hyaluronic gel was independent to the type of procedure, these figures being as follows: abortion, hysteroscopy, primary disorders/diseases such as abortion, IUA, submucosal myoma, endometrial polyps or mediastinum uterus. Furthermore, the hyaluronic gel improved pregnancy rates [ 132 ].…”
Section: Introduction Our Current Knowledge About the Asherman Symentioning
confidence: 99%
“…HA can bind to a large number of water molecules improving tissue hydration, increasing cell resistance to mechanical damage, and reducing post-traumatic formation of granulation and fibrous tissue. Due to its unique biocompatibility and enzymatic biodegradation, HA is often used to prevent postoperative adhesions [69,70]. HA gel significantly reduces the frequency of IUA after intrauterine surgery, regardless of the type of intervention or the presence of primary diseases.…”
Section: Clinical Usage Of Antiadhesive Polymers To Prevent Aschermanmentioning
confidence: 99%
“…These symptoms include abnormal uterine bleeding, amenorrhea, dysmenorrhea, infertility, abnormal placentation, and recurrent miscarriage [ 1 , 2 , 4 , 7 , 8 , 9 , 24 , 25 , 26 , 27 , 28 , 29 ]. As there is continuous progression in hysteroscopic surgeries and they are widely performed for the treatment of various kinds of intrauterine lesions, there is increased concern about IUA-associated morbidities and the subsequent significant impairment of reproductive performance in women of reproductive age [ 3 , 5 , 7 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Among these surgeries, hysteroscopic myomectomy is one of the best examples, since it is considered as the best choice of therapy in the management of women with submucosal myomas [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that in up to 62.5% of patients, IUA will recur after hysteroscopic adhesiolysis [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Taken together, this suggests the urgent need to focus on the primary prevention of IUA after intrauterine surgeries [ 3 , 5 , 7 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Several techniques have been proposed to prevent de novo IUA, which is postoperative adhesion without initial evidence of IUA at the same sites [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation